Matters of the Heart: Childhood Maltreatment, Religious Transitions, and Cardiovascular-Related Problems over the Life Course. (June 2023) - Upenieks, Laura; Thomas, Patricia A.
Objectives: Childhood maltreatment is associated with a higher risk of cardiovascular-related problems, the leading cause of death in the United States. Drawing from cumulative inequality theory, this study considers whether transitions in religious attendance moderate the deleterious impact of childhood maltreatment on long-term cardiovascular risk. Methods: We utilize over 35 years of prospective panel data from the National Longitudinal Study of Youth from the United States (1979–2015). Results: Our findings suggest that decreases in religious attendance between adolescence and adulthood (from high to low, and high to moderate attendance) were associated with elevated cardiovascular-related risk for those abused as children. Neither stable high attendance nor increases in attendance buffered against the impact of childhood abuse on cardiovascular-related problems. Discussion: We illustrate the importance of incorporating the role of stability and change in religious attendance across the life course and suggest directions for future research.